2011
DOI: 10.1111/j.1365-2699.2011.02558.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of phylogenetic assemblage structure along the elevational gradient for major hummingbird clades

Abstract: Aim We evaluated the hypothesis that, given niche conservatism, relatedness of co-occurring hummingbird species of a given clade will increase at greater distances from the elevation where it originated. We also used prior knowledge of flight biomechanics and feeding specialization of hummingbird species (family Trochilidae) to evaluate which environmental variables were important predictors of changes in phylogenetic structure for each hummingbird clade.Location Ecuador.Methods We compiled species lists for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 62 publications
(135 reference statements)
3
23
0
1
Order By: Relevance
“…Second, because the temperature niche is conserved in hummingbirds and we used temperature to define our species pools, it might be that particular clades are at least partly responsible for our observed patterns of evenness. Similar to our result, analyzing clades separately, Parra et al (2011) found patterns of phylogenetic evenness at high elevation for one of the two clades that radiated in the Andes (i.e., for brilliants but not coquettes) and for emeralds, which are also somewhat common in midelevation assemblages. Taken together, these results suggest that conservatism in the evolution of climatic niches, environmental filtering, and competitive interactions might interact to shape hummingbird assemblages, at least at high-and midelevation sites dominated by particular clades.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Second, because the temperature niche is conserved in hummingbirds and we used temperature to define our species pools, it might be that particular clades are at least partly responsible for our observed patterns of evenness. Similar to our result, analyzing clades separately, Parra et al (2011) found patterns of phylogenetic evenness at high elevation for one of the two clades that radiated in the Andes (i.e., for brilliants but not coquettes) and for emeralds, which are also somewhat common in midelevation assemblages. Taken together, these results suggest that conservatism in the evolution of climatic niches, environmental filtering, and competitive interactions might interact to shape hummingbird assemblages, at least at high-and midelevation sites dominated by particular clades.…”
Section: Discussionsupporting
confidence: 74%
“…This content downloaded from 130.225.098.210 on April 06, 2016 03:06:51 AM clades occurs at the highest and coldest elevations (Parra et al 2010(Parra et al , 2011. In addition, temperature and precipitation have been shown to influence the composition and spatial turnover of hummingbird species in studies conducted in the same region Weinstein et al 2014).…”
Section: Species Pools and Assemblage Structure 79mentioning
confidence: 99%
See 2 more Smart Citations
“…El hecho que el grupo de nectarívoros muestre mayores relaciones con otros grupos en su riqueza de especies se debe en parte a que la familia Trochilidae es un grupo que muestra cierta relación a los hábitats conservados y las altitudes (Parra, Rahbek, McGuire & Graham, 2011). Además, este grupo, en las zonas del Centro de Nicaragua presenta mayor riqueza de especies (Martínez-Sánchez, 2007), por lo que es un grupo de importancia ecológica en este ecosistema.…”
Section: Discussionunclassified